Research Note: A pilot study comparing White Leghorn and Isa Brown breeds under a free-range system on performance, egg quality and pasture characteristics - Mónica Gandarillas; Raimundo Elizalde; Sebastián Irazábal; Iván Calvache; Juan Pablo Keim; Oscar Balocchi (Poultry Science)
The aim of this study was to assess pasture growth, changes in botanical composition (BC), and the effects of pasture consumption on laying performance and egg quality in Isa Brown (IB) and White Leghorn (WL) hens. A total of thirty 18-week-old hens: 15 IB and 15 WL were used in this experiment which began after a two-week adaptation period. The hens were randomly assigned to three field replicates, each consisting of a 20 m² pasture plot with 5 hens per plot. Each hen was fed a balanced concentrate diet providing 120 g per hen per day. Pasture consumption and plant preference were monitored at 10-day intervals. After each monitoring period, the entire pasture plot was rotated. Pasture consumption, herbage mass and BC were assessed. External and internal egg quality were evaluated at the beginning and at the end of each 10-day period. Isa Brown hens consumed significantly more pasture compared to WL hens, with a mean consumption of 43.9 g per day versus 28.5 g per hen per day, respectively (P < 0.0001). The post-grazing pasture height was 4.31 cm higher in plots grazed by WL hens (10.9 cm) compared to those grazed by IB (6.7 cm). Moreover, botanical composition of the pasture before and after grazing indicated a clear preference for broadleaf species over legumes, and legumes were preferred over grass species by both genotypes. Egg quality results showed that IB vs. WL had greater egg weight (62.01 vs. 58.96 g), egg width (44.18 vs. 43.23 mm), egg shape index (78.96 vs. 77.65%), yolk color (10.13 vs. 8.97 units), yolk index (46.02 vs. 45.46%). In contrast, WL vs. IB was greater in eggshell percentage (9.87 vs. 9.71%), albumen index (13.27 vs. 10.89%) and haugh units (91.21 vs. 86.11). No difference for egg length were found between genotypes. These findings provide valuable insights into the grazing behavior and pasture preferences of different laying hen genotypes, as well as their potential impacts on pasture management and egg production systems.